PERBEDAAN JUMLAH ACTINOBACILLUS ACTINOMYCETEMCOMITANS PADA PERIODONTITIS AGRESIF BERDASARKAN JENIS KELAMIN - Rizki Amalina (Majalah Ilmiah Sultan Agung, 2011)
Prevalence of aggressive periodontitis showing the tendency to increase annually. Actinobacillus actinomycetemcomitans, is primary caused aggressive periodontitis, a pathogen not only in periodontal but also in some nonoral infections, possesses several virulence determinants which contribute to its ability to colonize the oral cavity, persist in the periodontal pocket, resist and evade host defenses, cause destruction to soft and hard tooth-supporting tissues, and interfere with host tissue repair after infection. This study is a cross sectionalstudy. Actinobacillus actinomycetemcomitans cultivated in AaGMBV dan measured by colony counter. The main sex hormones exerting influence on the periodontium are estrogen and progesterone. In women, during puberty, ovulation and pregnancy, there is an increase in the production of sex steroid hormones characterized by gingival enlargement, increased gingival bleeding andcrevicular fluid flow and microbial changes. The result of this study statistically analyzed by independent t-test because the member of each group totally separated. The analysis showed the value of p<0,05. It means that there are quantity differences between male and female. Keywords: Aggressive Periodontitis, Actinobacillus actinomycetemcomitans quantity, sex hormones